PENGARUH UKURAN PERUSAHAAN, TRANSFER PRICING DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PENGHINDARAN PAJAK: PENGHINDARAN PAJAK - Joice Yuli Ananda Ketaren (JEKOS (Jurnal Ekonomi Dan Sosial), 2025)
This study aims to analyze the influence of company size, transfer pricing, and institutional ownership on tax avoidance. The research was conducted by analyzing the financial statements of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The sample used in this study consists of 15 energy sector companies listed on the during the 2019–2023 period, selected using the purposive sampling technique. The data used in this research are secondary data in the form of financial statements from each company included in the sample.The variables used in this study are Company Size (X1) as the first independent variable, Transfer Pricing (X2) as the second independent variable, Institutional Ownership (X3) as the third independent variable, and Tax Avoidance (Y) as the dependent variable. Panel data regression is used as the research method in this study. The analysis of the research results was conducted with the assistance of the Eviews 12 software.The results of the study indicate that the appropriate model is the Fixed Effect Model (FEM). The findings show that Company Size has a negative partial effect on Tax Avoidance, Transfer Pricing has no partial effect on Tax Avoidance, Institutional Ownership has no partial effect on Tax Avoidance, and simultaneously, Company Size, Transfer Pricing, and Institutional Ownership have an effect on Tax Avoidance. Keywords:Company Size, Transfer Pricing, Institutional Ownership, Tax Avoidance